2007
DOI: 10.1074/jbc.m605213200
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8-independent Menthol-induced Ca2+ Release from Endoplasmic Reticulum and Golgi

Abstract: Menthol, a secondary alcohol produced by the peppermint herb, Mentha piperita, is widely used in the food and pharmaceutical industries as a cooling/soothing compound and odorant. It induces Ca 2؉ influx in a subset of sensory neurons from dorsal root and trigeminal ganglia, due to activation of TRPM8, a Ca 2؉ -permeable, cold-activated member of the TRP superfamily of cation channels. Menthol also induces Ca 2؉ release from intracellular stores in several TRPM8-expressing cell types, which has led to the sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
106
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 28 publications
9
106
1
2
Order By: Relevance
“…However, others have observed that some menthol-sensitive cells did not respond to cold (Nealen et al, 2003;Mahieu et al, 2006;Dhaka et al, 2007) and that the menthol responses in these cells were attributable to TRPM8-independent Ca 2ϩ release. Factors that might contribute to the discrepancy include the concentrations of menthol, the degree of cooling temperatures, the threshold setting for detecting Ca 2ϩ responses, and the cell types.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have observed that some menthol-sensitive cells did not respond to cold (Nealen et al, 2003;Mahieu et al, 2006;Dhaka et al, 2007) and that the menthol responses in these cells were attributable to TRPM8-independent Ca 2ϩ release. Factors that might contribute to the discrepancy include the concentrations of menthol, the degree of cooling temperatures, the threshold setting for detecting Ca 2ϩ responses, and the cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a series of recent in vivo studies using pharmacological antagonism and/or genetic deletion have established that TRPM8 plays a significant role in most individual thermoregulatory responses to cold: behavioral thermoregulation, BAT activation, peripheral vasoconstriction, and total metabolic response to cold (1,2,6,8,17,33). TRPM8 was also implicated in shivering thermogenesis in two studies using menthol as a TRPM8 agonist, which, however, were not conclusive due to possible TRPM8-independent actions of menthol (15,18,21,34). Despite this caveat, these and other studies seemed to have formed a prevailing implicit view in the literature that TRPM8 is a "universal" cold sensor, insofar as it controls every physiological response to cold.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM8 expression has been shown to be up-regulated in prostate cancer cells, as well as in several other nonprostatic primary cancers, including melanoma, colorectal carcinomas, and breast carcinomas (25,26). Studies have demonstrated that TRPM8 is expressed on the plasma and the endoplasmic reticulum (ER) membranes of cells, where it facilitates the influx or release of Ca 21 from extracellular sources and the ER stores, respectively (24,26,27). A study by Thebault and coworkers (24) established that TRPM8 was preferentially localized to the ER of androgen-responsive LNCaP prostate cancer cells.…”
mentioning
confidence: 99%